Topographic and hydrological controls on partial and full surges of Little Kluane Glacier, Yukon - Brittany Main; Luke Copland; Gwenn Elizabeth Flowers; Christine Fiona Dow; Wesley Van Wychen; Sergey Samsonov; William Kochtitzky (Journal of Glaciology)
We demonstrate that a ~20 km long valley glacier in the St. Elias Mountains, Yukon, can experience both partial and full surges, likely controlled by the presence of a topographic constriction and the formation and drainage of supraglacial lakes. Based on analysis of air photos, satellite images and field observations since the 1940s, we identify a full surge of ‘Little Kluane Glacier’ from 2013 to 2018, and a partial surge of just the upper north arm between 1963 and 1972. Repeat digital elevation models and velocity profiles indicate that the recent surge initiated from the upper north arm in 2013, which developed into a full surge of the main trunk from 2017 to 2018 with peak velocities of ~3600 m a−1 and frontal advance of ~1.7 km from May to September 2018. In 2016, a mass movement from the north arm to the main trunk generated a surface depression in a region immediately downstream of a topographic constriction, which promoted the formation and rapid drainage of supraglacial lakes to the glacier bed, and likely established the conditions to propel the initial partial surge into a full surge. Our results underscore the complex interplay between glacier geometry, surface hydrology and topography required to drive full surges of this glacier.